Preoperative long-course chemoradiotherapy plus adjuvant chemotherapy versus short-course radiotherapy without adjuvant chemotherapy both with delayed surgery for stage II–III resectable rectal cancer: 5-Year survival data of a randomized controlled trial - Laura Kairevičė; Tadas Latkauskas; Algimantas Tamelis; Aleksandras Petrauskas; Henrikas Paužas; Tadas Žvirblis; Laimonas Jaruševičius; Žilvinas Saladžinskas; Dainius Pavalkis; Rasa Jančiauskienė (Medicina, 2017)
Background and objective: At present, there are common recommendations for treatment for stage II–III resectable rectal cancer patients: preoperative conventional chemoradiotherapy (CRT) with delayed surgery in 6–8 weeks or preoperative short-course radiotherapy (SCRT) followed by immediate surgery. The aim of this study was to compare overall survival (OS) and disease-free survival (DFS) in two treatment groups: preoperative SCRT and CRT both with delayed surgery plus adjuvant chemotherapy in CRT arm. Materials and methods: A total of 150 patients were randomly assigned to two groups: 75 to CRT (preoperative conventional CRT, 50 Gy/25 fr with fluorouracil and leucovorin on the 1st and the 5th week of RT followed by TME surgery in 6–8 weeks and 4 cycles of adjuvant fluorouracil/leucovorin every 4 weeks; then follow-up) and 75 to SCRT (preoperative short-course RT, 25 Gy/5 fr followed by TME surgery in 6–8 weeks; then follow-up). The data of 140 patients (72 in CRT and 68 in SCRT group) were included in statistical analysis. Primary end points were OS and DFS. Results: Median follow-up was 60.5 (range, 5–108) months. The 5-year DFS was 67% in the CRT group (n = 72) and 45% in the SCRT group (n = 68) (P = 0.013; HR = 1.88; 95% CI, 1.13–3.12; P = 0.015). The 5-year OS was 79% and 62% in the CRT and SCRT groups, respectively (P = 0.015; HR = 2.05; 95% CI, 1.13–3.70; P = 0.017). The 5-year OS for intent-to-treat (ITT) population (n = 150) was 78% in the CRT and 58% in the SCRT group (P = 0.003; HR = 2.28; 95% CI, 1.30–4.00; P = 0.004). Conclusions: The 5-year DFS and OS were significantly better in the CRT than the SCRT group. For ITT population, OS was also significantly better after CRT versus SCRT.